4E interacting protein as a potential novel drug target for nucleoside analogues in trypanosoma brucei - Mabille, Dorien; Cardoso Santos, Camila; Hendrickx, Rik; Claes, Mathieu; Takac, Peter; Clayton, Christine; Hendrickx, Sarah; Hulpia, Fabian; Maes, Louis; VanCalenbergh, Serge; Caljon, Guy (Microorganisms, 2021)
Human African trypanosomiasis is a neglected parasitic disease for which the current treatment options are quite limited. Trypanosomes are not able to synthesize purines de novo and thus solely depend on purine salvage from the host environment. This characteristic makes players of the purine salvage pathway putative drug targets. The activity of known nucleoside analogues such as tubercidin and cordycepin led to the development of a series of C7-substituted nucleoside analogues. Here, we use RNA interference (RNAi) libraries to gain insight into the mode-of-action of these novel nucleoside analogues. Whole-genome RNAi screening revealed the involvement of adenosine kinase and 4E interacting protein into the mode-of-action of certain antitrypanosomal nucleoside analogues. Using RNAi lines and gene-deficient parasites, 4E interacting protein was found to be essential for parasite growth and infectivity in the vertebrate host. The essential nature of this gene product and involvement in the activity of certain nucleoside analogues indicates that it represents a potential novel drug target.